Epidemiological profile of vitiligo in Northern India - Suman Singh, Usha, Shyam Sunder Pandey (Journal of Applied Pharmaceutical Science)
Vitiligo is an acquired, progressive, common pigmentary disorder of the skin and hair characterized by well circumscribed milky white macules, devoid of identifiable melanocytes. From the Indian subcontinent the highest incidence has been reported in India. The aim of the study is to find the precipitating factor and clinical features of vitiligo patients in North India. Total of 275 subjects were enrolled for the study. The study was observational and was conducted over a two year period.118 were females while rest 82 were males. The most common type of vitiligo is vulgaris (45.5%). 78.5% cases had age of onset around the age of 40 years .40% cases were in 1-5 years duration of disease. Vitiligo does not show any significant association with any addiction. 22% patients are associated with the positive family history. 44% patients showed lower limb as a site of onset of vitiligo. There was no significant correlation with dietary habits in vitiligo. 59.5% cases belong to active vitiligo & rest of 40.5% is of stable category. 17.5% cases reported physical trauma as the precipitating factor. 12% patients were associated with thyroid disease. Majority of cases 68.5% were from urban areas. Clinoepidemiologic study in North India shows that vulgaris is the commonest subtype with female preponderance. Research on the presence of autoimmune disease; particularly thyroid disorder is of great interest.
Keywords: Vitiligo, epidemiology, thyroid, dietary habits.